Weather-proof decorative waterborne polyurethane mortar color sand self-leveling floor material

By using modified silica powder, copper/cobalt bimetallic MOFs, light stabilizers and fluoropolymers in water-based polyurethane mortar flooring materials, a multi-layer weather protection system is constructed, which solves the problem of poor weather resistance of existing materials in complex environments and achieves the performance improvement of high-performance flooring materials.

CN119912221AActive Publication Date: 2025-05-02BINSHI MATERIAL TECH (SHANGHAI) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510396627.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The existing water-based polyurethane mortar flooring materials have poor weather resistance, single functions, and small application range in complex use environments, making it difficult to meet the needs of high-performance flooring materials.

Method used

Modified silica powder, copper/cobalt bimetallic MOFs, light stabilizers and fluoropolymers with self-healing functions are used to build a multi-layer weather protection system to improve the weather resistance, mechanical properties and self-healing properties of the material.

Benefits of technology

It significantly improves the weather resistance of floor materials, extends service life, enhances mechanical properties and self-repair capabilities, and meets the needs of high-performance floor materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane mortar, in particular to a weather-proof decorative waterborne polyurethane mortar color sand self-leveling floor material. The weather-proof decorative type waterborne polyurethane mortar color sand self-leveling floor material is prepared from modified silicon dioxide powder, waterborne polyurethane emulsion, a dispersing agent, a curing agent, Portland cement, light resin color sand, a defoaming agent and a flatting agent, and modified silicon dioxide is modified through PS microspheres and a segmented copolymer P123 so that the modified silicon dioxide can have a high-porosity structure; meanwhile, a bimetallic MOFs material is adopted and compounded with a light stabilizer on silicon dioxide with high porosity, and then a fluorine-containing polymer with self-repairing performance is grafted to prepare the composite material. The weather-resistant decorative waterborne polyurethane mortar color sand self-leveling floor material has excellent weather resistance, good mechanical performance and certain self-repairing performance, and the application field of waterborne polyurethane mortar floor materials is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane mortar, in particular to a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material. Background Art

[0002] In the field of building decoration, waterborne polyurethane mortar floor materials are widely used due to their good decorative properties and ease of construction, but existing materials still have many shortcomings, which limits their further development and application.

[0003] On the one hand, the comprehensive performance of traditional waterborne polyurethane mortar flooring materials is difficult to meet the needs when facing complex use environments. For example, in outdoor or high-humidity, high-light indoor spaces, the floor is prone to aging, which not only affects the appearance, but also reduces the service life and increases maintenance costs, which hinders its application in special environments. On the other hand, as people's attention to multifunctional materials continues to increase, multifunctional waterborne polyurethane mortar flooring materials have become a research hotspot. However, existing products perform poorly in terms of performance, such as strength, wear resistance, chemical resistance and self-healing properties, and it is difficult to meet the market demand for high-performance flooring materials.

[0004] Therefore, it is urgent to develop a water-based polyurethane mortar colored sand self-leveling floor material that has excellent weather resistance and decorative properties as well as good mechanical properties and self-repairing properties, which is of great significance for promoting the development of the building decoration materials industry. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material to solve the problems of poor weather resistance, single function and small application range in existing water-based polyurethane mortar floor materials.

[0006] Based on the above purpose, the present invention provides a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material, comprising the following raw materials by weight: modified silicon dioxide powder: 30-40 parts, water-based polyurethane emulsion: 40-60 parts, dispersant: 0.5-1 part, curing agent: 6-8 parts, silicate cement: 20-30 parts, light resin colored sand: 30-40 parts, defoamer: 0.1-0.3 parts and leveling agent: 0.1-0.3 parts; The specific preparation method of the modified silicon dioxide powder is as follows: (1) Copper chloride, cobalt acetate, terephthalic acid, ethylene glycol and N,N-dimethylformamide are mixed, placed in a high-temperature hydrothermal reactor, heated to 150-170°C with stirring, reacted for 12-18 hours, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs; (2) Add PS microspheres to ethanol, sonicate for 30-50 min, then add ethyl orthosilicate, heat to 50-70°C, react for 18-24 h, cool to room temperature, filter, wash, and dry to obtain a mixture A; (3) Add the mixture A and block copolymer P123 obtained in (2) to ethanol, ultrasonicate for 20-40 minutes, then add tetraethyl orthosilicate, heat to 40-50°C, react for 8-12 hours, filter, wash, heat to 500-600°C in a muffle furnace at a heating rate of 1-5°C, keep warm for 3-5 hours, and cool to room temperature to obtain silicon dioxide with high porosity; (4) adding the high-porosity silica obtained in (3) to ethanol, ultrasonicating for 20-40 min, adding the copper / cobalt bimetallic MOFs and light stabilizer obtained in (1), heating to 25-35° C., reacting for 6-8 h, filtering, washing, and drying to obtain a mixture B; (5) Under nitrogen protection, add perfluoro-n-propyl vinyl ether, trifluorochloroethylene, 3-methylacrylamidophenylboronic acid, cystine dimethyl ester and sodium dodecyl sulfate into deionized water, stir for 20-40 min, then add 2-cyanopropyl-2-benzodisulfide and potassium persulfate, heat to 60-80°C, react for 8-12 h, cool to room temperature, add hydroquinone, stir for 30-40 min, centrifuge, wash and dry to obtain a fluorine-containing polymer containing disulfide bonds and borate ester bonds; (6) Mix the mixture B obtained in (4), the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5), and N,N-dimethylformamide, heat to 80-100° C., react for 8-12 hours, cool to room temperature, centrifuge, wash, dry, and pass through a 300-400 mesh sieve to obtain modified silica powder.

[0007] Preferably, the dispersant refers to DX-915 or DX-407 produced by Metachemie.

[0008] Preferably, the curing agent is toluene diisocyanate or isophorone diisocyanate.

[0009] Preferably, the defoamer refers to BYK-052 or BYK-053 produced by BYK.

[0010] Preferably, the leveling agent refers to EFKA-3777 produced by Efka or BYK-333 produced by BYK.

[0011] Preferably, in the (1), the weight ratio of copper chloride, cobalt acetate, terephthalic acid, ethylene glycol and N,N-dimethylformamide is 3-6:1-2:0.6-1:3-5:15-25. The prepared copper / cobalt bimetallic MOFs can effectively shield the degradation of ultraviolet light due to its unique structure, thereby enhancing the stability of the material.

[0012] Preferably, in said (2), the weight ratio of PS microspheres, tetraethyl orthosilicate and ethanol is 0.8-1:0.9-1.5:10-14.

[0013] Preferably, the particle size of the PS microspheres in (2) is 50-100 nm. The size of the PS microspheres affects the size of the macropores of the modified silica. Appropriate pores can provide a certain structural support while providing a larger surface area, so that the pore structure of the silica will not collapse easily.

[0014] Preferably, the weight ratio of the mixture A, block copolymer P123, ethyl orthosilicate and ethanol in (3) is 1:0.1-0.2:1-1.2:10-14. The addition of block copolymer P123 enables silica to obtain a richer mesoporous structure on the basis of the macroporous structure, thereby further improving the porosity of silica.

[0015] Preferably, the weight ratio of the high-porosity silica, copper / cobalt bimetallic MOFs, light stabilizer and ethanol in (4) is 1:0.2-0.4:0.3-0.5:10-14.

[0016] Preferably, the light stabilizer in (4) is prepared by mixing nano zinc oxide and nano cerium oxide in a weight ratio of 2:1. Nano zinc oxide and nano cerium oxide can absorb ultraviolet rays and inhibit photo-oxidative degradation.

[0017] Preferably, in (5), the weight ratio of perfluoro-n-propyl vinyl ether, chlorotrifluoroethylene, 3-methylacrylamidophenylboric acid, dimethyl cysteine, sodium dodecyl sulfate, 2-cyanopropyl-2-ylbenzodisulfide, potassium persulfate, hydroquinone and deionized water is 1:0.5-1:0.2-0.5:0.2-0.5:0.01-0.05:0.005-0.015:0.002-0.01:0.01-0.03:15-25.

[0018] Preferably, the weight ratio of the mixture B, the fluorinated polymer containing disulfide bonds and borate bonds, and N,N-dimethylformamide in (6) is 1:0.2-0.4:10-14. The disulfide bond provides a certain self-healing ability for the material, and the isocyanate bond can provide a stronger chemical bond when the fluorinated polymer is combined with silica.

[0019] Preferably, the weight ratio of the aqueous polyurethane emulsion, dispersant, modified silica powder, curing agent, silicate cement, lightweight resin colored sand, defoamer and leveling agent in (7) is 40-60: 0.5-1: 30-40: 6-8: 20-30: 30-40: 0.1-0.3: 0.1-0.3.

[0020] Furthermore, the present invention also provides a method for preparing the above-mentioned weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material, comprising the following process: adding a dispersant to the water-based polyurethane emulsion, stirring for 10-20 minutes, adding modified silicon dioxide powder, stirring for 20-30 minutes, and then adding a curing agent, silicate cement, lightweight resin colored sand, a defoaming agent and a leveling agent. After mixing and stirring for 1-3 hours, the mixture is applied to the coated surface with a serrated scraper. After curing, a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material is obtained.

[0021] Beneficial effects of the present invention: 1. Excellent weather resistance: The floor material of the present invention constructs a multi-level weather protection system through copper / cobalt bimetallic MOFs, light stabilizers and fluorinated polymers with self-healing functions. With its unique structure, copper / cobalt bimetallic MOFs effectively shield the degradation of ultraviolet light and enhance the stability of the material; the light stabilizer effectively absorbs ultraviolet light and inhibits photo-oxidative degradation; and the fluorinated polymer gives the material good chemical resistance and weather resistance. These components work synergistically to significantly reduce the impact of light, temperature and humidity changes on the material, so that the floor maintains stable color during long-term use, is not prone to aging, fading and other phenomena, and greatly extends the service life.

[0022] 2. Excellent mechanical properties: The high porosity of silica in the material effectively improves the structural stability and hardness of the material. At the same time, the curing agent, silicate cement and other ingredients work together to enhance the bonding force between the coating and the substrate. This makes the floor material not only have excellent wear resistance, but also maintain a smooth surface and intact structure when subjected to external forces such as friction and heavy pressure. It also has strong adhesion and is not prone to problems such as coating shedding and delamination, ensuring the reliability and stability of the floor in various usage scenarios.

[0023] 3. Possessing self-repairing function: The light stabilizer and fluorine-containing polymer with self-repairing ability contained in the floor material of the present invention endow the material with self-repairing ability. When scratches or minor damage appear on the surface of the material, the components in the light stabilizer can absorb energy and inhibit further expansion of the damage; at the same time, the disulfide bonds in the fluorine-containing polymer with self-repairing ability undergo reversible reactions under certain conditions, prompting the internal structure of the material to rearrange, automatically fill scratches and damaged parts, restore the integrity and performance of the material, reduce daily maintenance costs, and improve the use value of the floor. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0025] The sources of the reagents used in the embodiments of the present invention are as follows: Cupric chloride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a product number of C106774 and a purity of 99%; cobalt acetate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of C805752 and a purity of 98%; terephthalic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a product number of P420255 and a purity of 99%; ethylene glycol was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a product number of E103319 and a purity of 98%; PS microspheres were purchased from Suzhou Nanotech Co., Ltd. with a particle size of 50-100 nm; tetraethyl orthosilicate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a product number of T110593 and a purity of 98%; block polymer P123 was purchased from Tianjin Xien Nano zinc oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a product number of P-10691 and a purity of 99.8%; nano cerium oxide was purchased from Shanghai Yien Chemical Technology Co., Ltd., with a product number of R008052 and a purity of 99.5%; perfluoro-n-propyl vinyl ether was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a product number of P857062 and a purity of 98%; trifluorochloroethylene was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a product number of C889791 and a purity of 99.9%; 3-methacrylamidophenylboronic acid was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a product number of M856878 and a purity of 98% , cystine dimethyl ester was purchased from Guangzhou Jiatu Technology Co., Ltd. with a purity of 98%; sodium dodecyl sulfate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of S850167 and a purity of 97%; 2-cyanopropyl-2-ylbenzodisulfide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of C885875 and a purity of 97%; potassium persulfate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a product number of P112193 and a purity of 99%; hydroquinone was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of H811112 and a purity of 99%; p-toluenesulfonic acid was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a product number of T823839 and a purity of 99%; water-based polyurethane emulsion Liquid was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with the item number A909856 and solid content of 40%; Portland cement was purchased from Tangshan Hongye Special Cement Co., Ltd. with the model P·I type; toluene diisocyanate was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with the item number T823849 and purity of 98%; isophorone diisocyanate was purchased from Shanghai McLean Biochemical Technology Co., Ltd. with the item number I811865 and purity of 99%; lightweight resin colored sand was purchased from Dongguan Shili Surface Treatment Materials Co., Ltd. with the specification of 7-320 mesh; Cu-MOFs was purchased from Changsha Yimo Biotechnology Co., Ltd. with a purity of 98%; silicon dioxide was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd. with a purity of 99%.

[0026] Embodiment 1: A specific preparation scheme of a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material, comprising the following steps: (1) 80 g of copper chloride, 30 g of cobalt acetate, 16 g of terephthalic acid, 80 g of ethylene glycol and 400 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave, heated to 150 °C with stirring, reacted for 12 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs; (2) Add 320 g of PS microspheres with a particle size of 50 nm to 3.2 kg of ethanol, ultrasonicate for 30 min, then add 350 g of ethyl orthosilicate, heat to 50 ° C, react for 18 h, cool to room temperature, filter, wash, and dry to obtain a mixture A; (3) 400 g of the mixture A obtained in (2) and 40 g of the block copolymer P123 were added to 4 kg of ethanol, ultrasonicated for 20 min, and then 400 g of ethyl orthosilicate was added. The temperature was raised to 40 °C, reacted for 8 h, filtered, washed, and heated to 500 °C in a muffle furnace at a heating rate of 1 °C, kept warm for 3 h, and cooled to room temperature to obtain silica with high porosity and a pore volume of 0.53 cm 3 / g; (4) Add 450 g of high-porosity silica obtained in (3) to 4.5 kg of ethanol, ultrasonicate for 20 min, add 90 g of copper / cobalt bimetallic MOFs obtained in (1) and 135 g of light stabilizer (nano zinc oxide: nano cerium oxide = 2:1), heat to 25-35° C., react for 6-8 h, filter, wash, and dry to obtain a mixture B; (5) Under nitrogen protection, 80 g of perfluoroalkyl vinyl ether, 40 g of trifluorochloroethylene, 16 g of 3-methylacrylamidophenylboronic acid, 16 g of cystine dimethyl ester and 0.8 g of sodium dodecyl sulfate were added to 1.2 kg of deionized water, stirred for 20 min, and then 0.4 g of 2-cyanopropyl-2-benzodisulfide and 0.16 g of potassium persulfate were added. The temperature was raised to 60 ° C. and reacted for 8 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 30 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (6) 400 g of the mixture B obtained in (4), 80 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5) and 4 kg of N,N-dimethylformamide were mixed, the temperature was raised to 80° C., reacted for 8 h, cooled to room temperature, centrifuged, washed, dried, and passed through a 300-mesh sieve to obtain modified silica powder; (7) Add 5 g of dispersant DX-915 to 400 g of waterborne polyurethane emulsion and stir for 10 min. Add 300 g of modified silica powder obtained in (6) and stir for 20 min. Then add 60 g of isophorone diisocyanate, 200 g of silicate cement, 300 g of lightweight resin colored sand, 1 g of defoamer BYK-052 and 1 g of leveling agent EFKA-3777. Mix and stir for 1 h, then apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0027] Embodiment 2: A specific preparation scheme of a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material, comprising the following steps: (1) 120 g of copper chloride, 45 g of cobalt acetate, 24 g of terephthalic acid, 120 g of ethylene glycol and 600 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave. The mixture was heated to 160 °C with stirring, reacted for 15 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs. (2) 360 g of PS microspheres with a particle size of 80 nm were added to 4.8 kg of ethanol, and ultrasonicated for 40 min. Then, 480 g of ethyl orthosilicate was added, and the temperature was raised to 60 ° C. and reacted for 21 h. After cooling to room temperature, the mixture was filtered, washed, and dried to obtain a mixture A. (3) 400 g of the mixture A obtained in (2) and 60 g of the block copolymer P123 were added to 4.8 kg of ethanol, ultrasonicated for 30 min, and then 440 g of ethyl orthosilicate was added. The temperature was raised to 45 °C, reacted for 10 h, filtered, washed, and heated to 550 °C in a muffle furnace at a heating rate of 3 °C, kept warm for 4 h, and cooled to room temperature to obtain silica with high porosity and a pore volume of 0.59 cm 3 / g; (4) 450 g of high-porosity silica obtained in (3) was added to ethanol, ultrasonicated for 30 min, 135 g of copper / cobalt bimetallic MOFs obtained in (1) and 180 g of light stabilizer (nano-zinc oxide: nano-cerium oxide = 2:1) were added, the temperature was raised to 30° C., reacted for 7 h, filtered, washed, and dried to obtain a mixture B; (5) Under nitrogen protection, 120 g of perfluoroalkyl vinyl ether, 90 g of chlorotrifluoroethylene, 42 g of 3-methylacrylamidophenylboronic acid, 42 g of cystine dimethyl ester and 4.2 g of sodium dodecyl sulfate were added to 2.4 kg of deionized water and stirred for 30 min. Then, 1.2 g of 2-cyanopropyl-2-benzodisulfide and 0.72 g of potassium persulfate were added. The temperature was raised to 70 ° C. and the reaction was carried out for 10 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 35 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (6) 400 g of the mixture B obtained in (4), 120 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5), and N,N-dimethylformamide were mixed, the temperature was raised to 90° C., the reaction was carried out for 10 h, the mixture was cooled to room temperature, centrifuged, washed, dried, and passed through a 350-mesh sieve to obtain modified silica powder; (7) Add 7.5 g of dispersant DX-915 to 500 g of waterborne polyurethane emulsion and stir for 15 min. Add 350 g of modified silica powder obtained in (6) and stir for 25 min. Then add 70 g of isophorone diisocyanate, 250 g of silicate cement, 350 g of lightweight resin colored sand, 2 g of defoamer BYK-052 and 2 g of leveling agent EFKA-3777. Mix and stir for 2 h, and apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0028] Embodiment 3: A specific preparation scheme of a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material, comprising the following steps: (1) 180 g of copper chloride, 60 g of cobalt acetate, 30 g of terephthalic acid, 150 g of ethylene glycol and 750 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave. The mixture was heated to 170 °C with stirring, reacted for 18 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs. (2) 300 g of PS microspheres with a particle size of 100 nm were added to 5.2 kg of ethanol, ultrasonicated for 50 min, and then 450 g of ethyl orthosilicate was added. The temperature was raised to 70 ° C. and reacted for 24 h. After cooling to room temperature, the mixture was filtered, washed, and dried to obtain a mixture A. (3) 500 g of compound A and 100 g of block copolymer P123 obtained in (2) were added to ethanol, ultrasonicated for 40 min, and then 600 g of tetraethyl orthosilicate was added. The temperature was raised to 50 °C, reacted for 12 h, filtered, washed, and heated to 600 °C in a muffle furnace at a heating rate of 5 °C, kept warm for 5 h, and cooled to room temperature to obtain silica with high porosity and a pore volume of 0.56 cm 3 / g; (4) 500 g of the high-porosity silica obtained in (3) was added to 7 kg of ethanol, and ultrasonicated for 40 min. 200 g of the copper / cobalt bimetallic MOFs obtained in (1) and 250 g of a light stabilizer (nano-zinc oxide: nano-cerium oxide = 2:1) were added. The temperature was raised to 35 °C, and the reaction was carried out for 8 h. After filtering, washing, and drying, a mixture B was obtained. (5) Under nitrogen protection, add 100 g of perfluoro-n-propyl vinyl ether, 100 g of trifluorochloroethylene, 50 g of 3-methylacrylamidophenylboronic acid, 50 g of cystine dimethyl ester and 5 g of sodium dodecyl sulfate to 2.5 kg of deionized water, stir for 40 min, then add 1.5 g of 2-cyanopropyl-2-benzodisulfide and 1 g of potassium persulfate, heat to 80 ° C, react for 12 h, cool to room temperature, add 3 g of hydroquinone, stir for 40 min, centrifuge, wash and dry to obtain a fluorine-containing polymer containing disulfide bonds and borate ester bonds; (6) 500 g of the mixture B obtained in (4), 100 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5) and 7 kg of N,N-dimethylformamide were mixed, heated to 100 °C, reacted for 12 h, cooled to room temperature, centrifuged, washed, dried, and passed through a 400-mesh sieve to obtain modified silica powder; (7) Add 10 g of dispersant DX-915 to 600 g of waterborne polyurethane emulsion and stir for 20 min. Add 400 g of modified silica powder obtained in (6) and stir for 30 min. Then add 80 g of isophorone diisocyanate, 300 g of silicate cement, 400 g of lightweight resin colored sand, 3 g of defoamer BYK-052 and 3 g of leveling agent EFKA-3777. Mix and stir for 3 h, and apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0029] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the copper / cobalt bimetallic MOF bimetallic MOF is replaced by an ordinary monometallic MOF, and the specific preparation process is as follows: A specific preparation scheme for a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material comprises the following steps: (1) 360 g of PS microspheres with a particle size of 80 nm were added to 4.8 kg of ethanol, and ultrasonicated for 40 min. Then, 480 g of ethyl orthosilicate was added, and the temperature was raised to 60 ° C. and reacted for 21 h. After cooling to room temperature, the mixture was filtered, washed, and dried to obtain a mixture A; (2) 400 g of the mixture A obtained in (1) and 60 g of the block copolymer P123 were added to 4.8 kg of ethanol, ultrasonicated for 30 min, and then 440 g of ethyl orthosilicate was added. The temperature was raised to 45 °C, reacted for 10 h, filtered, washed, and heated to 550 °C in a muffle furnace at a heating rate of 3 °C, kept warm for 4 h, and cooled to room temperature to obtain silica with high porosity and a pore volume of 0.54 cm 3 / g; (3) 450 g of high-porosity silica obtained in (2) was added to ethanol, ultrasonicated for 30 min, 135 g of Cu-MOFs and 180 g of light stabilizer (nano zinc oxide: nano cerium oxide = 2:1) were added, the temperature was raised to 30 ° C, reacted for 7 h, filtered, washed, and dried to obtain a mixture B; (5) Under nitrogen protection, 120 g of perfluoroalkyl vinyl ether, 90 g of chlorotrifluoroethylene, 42 g of 3-methylacrylamidophenylboronic acid, 42 g of cystine dimethyl ester and 4.2 g of sodium dodecyl sulfate were added to 2.4 kg of deionized water and stirred for 30 min. Then, 1.2 g of 2-cyanopropyl-2-benzodisulfide and 0.72 g of potassium persulfate were added. The temperature was raised to 70 ° C. and the reaction was carried out for 10 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 35 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (6) 400 g of the mixture B obtained in (4), 120 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5), and N,N-dimethylformamide were mixed, the temperature was raised to 90° C., the reaction was carried out for 10 h, the mixture was cooled to room temperature, centrifuged, washed, dried, and passed through a 350-mesh sieve to obtain modified silica powder; (7) Add 7.5 g of dispersant DX-915 to 500 g of waterborne polyurethane emulsion and stir for 15 min. Add 350 g of modified silica powder obtained in (6) and stir for 25 min. Then add 70 g of isophorone diisocyanate, 250 g of silicate cement, 350 g of lightweight resin colored sand, 2 g of defoamer BYK-052 and 2 g of leveling agent EFKA-3777. Mix and stir for 2 h, and apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0030] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the modified silica is not subjected to PS microspheres to prepare macropores, and the specific preparation process is as follows: A specific preparation scheme for a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material comprises the following steps: (1) 120 g of copper chloride, 45 g of cobalt acetate, 24 g of terephthalic acid, 120 g of ethylene glycol and 600 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave. The mixture was heated to 160 °C with stirring, reacted for 15 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs. (2) Add 90 g of block copolymer P123 to 4.8 kg of ethanol, ultrasonicate for 30 min, then add 660 g of tetraethyl orthosilicate, heat to 45 °C, react for 10 h, filter, wash, heat to 550 °C in a muffle furnace at a heating rate of 3 °C, keep warm for 4 h, and cool to room temperature to obtain porous silica with a pore volume of 0.36 cm3 / g; (3) 450 g of porous silica obtained in (2) was added to ethanol, ultrasonicated for 30 min, 135 g of copper / cobalt bimetallic MOFs obtained in (1) and 180 g of light stabilizer (nano zinc oxide: nano cerium oxide = 2:1) were added, the temperature was raised to 30° C., reacted for 7 h, filtered, washed, and dried to obtain a mixture A; (4) Under nitrogen protection, 120 g of perfluoroalkyl vinyl ether, 90 g of chlorotrifluoroethylene, 42 g of 3-methylacrylamidophenylboronic acid, 42 g of cystine dimethyl ester and 4.2 g of sodium dodecyl sulfate were added to 2.4 kg of deionized water and stirred for 30 min. Then, 1.2 g of 2-cyanopropyl-2-benzodisulfide and 0.72 g of potassium persulfate were added. The temperature was raised to 70 ° C. and reacted for 10 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 35 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (5) 400 g of the mixture A obtained in (3), 120 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5), and N,N-dimethylformamide were mixed, the temperature was raised to 90° C., the reaction was performed for 10 h, the mixture was cooled to room temperature, centrifuged, washed, dried, and passed through a 350-mesh sieve to obtain modified silica powder; (6) Add 7.5 g of dispersant DX-915 to 500 g of waterborne polyurethane emulsion and stir for 15 min. Add 350 g of modified silica powder obtained in (5) and stir for 25 min. Then add 70 g of isophorone diisocyanate, 250 g of silicate cement, 350 g of lightweight resin colored sand, 2 g of defoamer BYK-052 and 2 g of leveling agent EFKA-3777. After mixing and stirring for 2 h, apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0031] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the modified silica is not prepared into mesopores through the block copolymer P123, and the specific preparation process is as follows: A specific preparation scheme for a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material comprises the following steps: (1) 120 g of copper chloride, 45 g of cobalt acetate, 24 g of terephthalic acid, 120 g of ethylene glycol and 600 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave. The mixture was heated to 160 °C with stirring, reacted for 15 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs. (2) 360 g of PS microspheres with a particle size of 80 nm were added to 4.8 kg of ethanol, and ultrasonicated for 40 min. Then 480 g of ethyl orthosilicate was added, and the temperature was raised to 60 °C, and the reaction was carried out for 21 h. After cooling to room temperature, the mixture was filtered and washed. The temperature was raised to 550 °C at a heating rate of 3 °C in a muffle furnace, and the temperature was kept at this temperature for 4 h. After cooling to room temperature, silica with pores was obtained, and the pore volume was 0.27 cm 3 / g; (3) 450 g of porous silica obtained in (2) was added to ethanol, ultrasonicated for 30 min, 135 g of copper / cobalt bimetallic MOFs obtained in (1) and 180 g of light stabilizer (nano zinc oxide: nano cerium oxide = 2:1) were added, the temperature was raised to 30° C., reacted for 7 h, filtered, washed, and dried to obtain a mixture A; (4) Under nitrogen protection, 120 g of perfluoroalkyl vinyl ether, 90 g of chlorotrifluoroethylene, 42 g of 3-methylacrylamidophenylboronic acid, 42 g of cystine dimethyl ester and 4.2 g of sodium dodecyl sulfate were added to 2.4 kg of deionized water and stirred for 30 min. Then, 1.2 g of 2-cyanopropyl-2-benzodisulfide and 0.72 g of potassium persulfate were added. The temperature was raised to 70 ° C. and reacted for 10 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 35 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (5) 400 g of the mixture A obtained in (3), 120 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (4), and N,N-dimethylformamide were mixed, the temperature was raised to 90° C., the reaction was performed for 10 h, the mixture was cooled to room temperature, centrifuged, washed, dried, and passed through a 350-mesh sieve to obtain modified silica powder; (6) Add 7.5 g of dispersant DX-915 to 500 g of waterborne polyurethane emulsion and stir for 15 min. Add 350 g of modified silica powder obtained in (6) and stir for 25 min. Then add 70 g of isophorone diisocyanate, 250 g of silicate cement, 350 g of lightweight resin colored sand, 2 g of defoamer BYK-052 and 2 g of leveling agent EFKA-3777. After mixing and stirring for 2 h, apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0032] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the modified silica is replaced by ordinary silica, and the specific preparation process is as follows: A specific preparation scheme for a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material comprises the following steps: (1) 120 g of copper chloride, 45 g of cobalt acetate, 24 g of terephthalic acid, 120 g of ethylene glycol and 600 g of N,N-dimethylformamide were mixed and placed in a high-temperature hydrothermal autoclave. The mixture was heated to 160 °C with stirring, reacted for 15 h, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs. (2) Add 450 g of silica to ethanol, sonicate for 30 min, add 135 g of copper / cobalt bimetallic MOFs obtained in (1) and 180 g of light stabilizer (nano zinc oxide: nano cerium oxide = 2:1), heat to 30 °C, react for 7 h, filter, wash, and dry to obtain a mixture A; (3) Under nitrogen protection, 120 g of perfluoroalkyl vinyl ether, 90 g of chlorotrifluoroethylene, 42 g of 3-methylacrylamidophenylboronic acid, 42 g of cystine dimethyl ester and 4.2 g of sodium dodecyl sulfate were added to 2.4 kg of deionized water and stirred for 30 min. Then, 1.2 g of 2-cyanopropyl-2-benzodisulfide and 0.72 g of potassium persulfate were added. The temperature was raised to 70 ° C. and reacted for 10 h. After cooling to room temperature, 2.4 g of hydroquinone was added and stirred for 35 min. After centrifugation, washing and drying, a fluorinated polymer containing disulfide bonds and borate ester bonds was obtained. (4) 400 g of the mixture A obtained in (2), 120 g of the fluorinated polymer containing disulfide bonds and borate bonds obtained in (3), and N,N-dimethylformamide were mixed, heated to 90° C., reacted for 10 h, cooled to room temperature, centrifuged, washed, dried, and passed through a 350-mesh sieve to obtain modified silica powder; (5) Add 7.5 g of dispersant DX-915 to 500 g of waterborne polyurethane emulsion and stir for 15 min. Add 350 g of modified silica powder obtained in (4) and stir for 25 min. Then add 70 g of isophorone diisocyanate, 250 g of silicate cement, 350 g of lightweight resin colored sand, 2 g of defoamer BYK-052 and 2 g of leveling agent EFKA-3777. After mixing and stirring for 2 h, apply the mixture to the coated surface with a serrated scraper. After curing, a weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material is obtained.

[0033] Performance Test: According to the preparation methods, weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor materials of the same size were prepared from Examples 1-3 and Comparative Examples 1-4 as test samples.

[0034] Weathering test: The test was conducted in accordance with the conditions specified in the standard GB / T 1865-2009. During the test, the irradiance of the xenon arc lamp, the blackboard temperature, the relative humidity, the water spraying cycle and other parameters of each sample were kept consistent, simulating the changes in light, temperature and humidity in the natural environment. The test lasted for 2000 hours, and the sample was taken out and the color change of the sample before and after aging was measured using a colorimeter. The experimental data are shown in Table 1. Then the tested samples are subjected to the adhesion test method according to the standard GB / T 9286-2021 by the cross-cut method to detect the adhesion level of the test pieces after aging. The rating is divided into 0-5 levels, and level 0 is the best adhesion state. The experimental data are shown in Table 1.

[0035] Wear resistance test: Test according to GB / T 1768-2006. Use a balance with an accuracy of 0.001g to weigh the mass of the specimen before and after friction, and calculate the mass loss rate. , the experimental results are shown in Table 1.

[0036] Self-repair experiment: Use a sharp tool to scratch a 0.5mm deep and 2cm long scratch on the surface of the prepared floor material specimen, place the scratched specimen in a constant temperature and humidity chamber at 25℃ and 50% relative humidity, and let the material repair naturally. After seven days, observe the material's repair status and the repair rate. , the experimental results are shown in Table 1.

[0037] Pore ​​volume: measured by elliptical porosimetry. The results are shown in Table 1.

[0038] Table 1 Performance test results

[0039] Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor materials of Examples 1-3 all exhibit good weather resistance, high wear resistance and good self-repairing properties. Among them, the comprehensive performance of Example 2 is the best, and the pore volume reaches 0.59 cm 3 / g, which shows that the introduction of copper / cobalt bimetallic MOFs used in the present invention significantly improves the catalytic activity and stability of the material through the synergistic effect between metals, effectively delays the degradation caused by ultraviolet rays, and the modified silica loads light stabilizers and MOFs through high porosity to achieve precise distribution of functional components. The reasonable design of pore structure is the key to functional synergy. Finally, the fluorinated polymers with disulfide bonds and borate bonds give the material dynamic self-healing ability. This fluorinated polymer is grafted on the modified silica to obtain a larger surface area, which is easier to contact with the external environment, thereby better playing a role.

[0040] As can be seen from Table 1, the weather resistance, wear resistance and self-healing properties of Comparative Example 1 compared to Example 2 are all reduced, and the adhesion level is reduced. This may be because the copper / cobalt bimetallic MOFs can produce a synergistic effect by virtue of their unique bimetallic structure. This synergistic effect can enhance the material's ability to shield ultraviolet rays and effectively inhibit photooxidative degradation, thereby significantly improving the stability and weather resistance of the material. In terms of wear resistance, bimetallic MOFs can synergize with other ingredients to enhance the bonding force between the coating and the substrate, and help to improve the overall structural stability of the material. In terms of self-healing performance, the weather-resistant protection system constructed by bimetallic MOFs can provide a stable environment for the disulfide bonds in the fluoropolymer to exert their self-healing function. Ordinary monometallic MOFs cannot provide such favorable conditions, and the self-healing function of the fluoropolymer is affected, and the self-healing rate of the material is reduced.

[0041] It can be seen from Table 1 that the weather resistance, wear resistance and self-healing property of Comparative Example 2 are significantly decreased compared with Example 2, and the adhesion level is also reduced. This may be because the macroporous structure constructed by PS microspheres is the key link in forming high porosity. Without this key link, the pore volume is reduced to 0.36 cm 3 / g. The macropores in Example 2 provide sufficient space for the subsequent loading of functional components such as light stabilizers and bimetallic MOFs, which is conducive to the uniform dispersion and efficient function of these components. In terms of weather resistance, the macroporous structure enables the light stabilizer to better contact with external light, enhances the absorption and shielding effect of ultraviolet rays, and at the same time, a reasonable macroporous structure helps to enhance the overall structural stability of the material, so that the internal structure of the material can be better maintained intact when subjected to external forces such as friction. The macroporous structure also provides a larger activity space and reaction sites for the disulfide bonds in the fluoropolymer, so that it can more effectively undergo reversible reactions for repair when the material is damaged. The lack of macropores in Comparative Example 2 limits the self-repair reaction of the fluoropolymer, resulting in a lower repair rate. Finally, in terms of adhesion, the macroporous structure can increase the contact area and mechanical bite between the coating and the substrate, thereby enhancing adhesion.

[0042] As can be seen from Table 1, the weather resistance, wear resistance, self-repair rate and adhesion level of Comparative Example 3 are not as good as those of Example 2. This may be because in the process of Example 2, the block copolymer P123 acts as a template, accurately controls the formation of a mesoporous structure, and enriches the porosity of silica. Mesopores play a vital role in increasing porosity. Without mesopores to adjust pores, the pore volume of the obtained silica drops to 0.27 cm 3 / g. The appropriate pore size and high specific surface area in Example 2 greatly promote the uniform dispersion and efficient loading of functional components such as light stabilizers and copper / cobalt bimetallic MOFs. In terms of weather resistance, the mesoporous structure allows the light stabilizer to be fully exposed and absorb ultraviolet rays more effectively. At the same time, the bimetallic MOFs use the good dispersion of mesopores to better shield ultraviolet rays and inhibit the photo-oxidative degradation of the material. In terms of wear resistance, the mesopores enhance the structural stability and toughness of the material. When subjected to external forces such as friction and heavy pressure, the mesoporous structure can effectively disperse stress and reduce local damage. In terms of self-healing performance, the mesopores provide more reaction sites and diffusion channels for disulfide bonds in fluoropolymers. When the material is damaged, these chemical bonds can move and react quickly through the mesopores to achieve self-repair. In terms of adhesion, the mesoporous structure increases the contact area and interaction force between the coating and the substrate, thereby improving adhesion.

[0043] It can be seen from Table 1 that the performance of Comparative Example 4 is significantly reduced compared with that of Example 2. This may be because the common silica used in Comparative Example 4 has a small pore volume of only 0.03 cm 3 / g, the modified silica prepared in Example 2 has a unique high porosity structure, and the surface-rich porosity and pore sizes of different sizes can load key functional components such as bimetallic MOFs and light stabilizers, and provide them with a stable and conducive environment for function. The pore structure can make the light stabilizer fully exposed to external light, enhance the absorption and scattering ability of ultraviolet rays, and at the same time, the bimetallic MOFs can effectively shield ultraviolet rays in the pores, inhibiting the photo-oxidative degradation of the material. When the material is rubbed, this high-porosity structure can also disperse stress and reduce surface damage. At the same time, in the absence of this modification, the lower specific surface area is also difficult to allow compounds with self-repairing ability to contact the damaged position, limiting the performance of the self-repairing function, and finally the special structure of the modified silica increases the contact area and mechanical bite between the coating and the substrate, so that the coating is closely combined with the substrate, and the ordinary silica structure is simple and cannot provide sufficient bonding force, resulting in poor adhesion between the coating and the substrate.

[0044] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material, characterized in that: The invention comprises the following raw materials in weight fractions: modified silicon dioxide powder: 30-40 parts, water-based polyurethane emulsion: 40-60 parts, dispersant: 0.5-1 parts, curing agent: 6-8 parts, silicate cement: 20-30 parts, light resin colored sand: 30-40 parts, defoamer: 0.1-0.3 parts and leveling agent: 0.1-0.3 parts; The specific preparation method of the modified silicon dioxide powder is as follows: (1) Copper chloride, cobalt acetate, terephthalic acid, ethylene glycol and N,N-dimethylformamide are mixed, placed in a high-temperature hydrothermal reactor, heated to 150-170°C with stirring, reacted for 12-18 hours, cooled to room temperature, filtered, washed and dried to obtain copper / cobalt bimetallic MOFs; (2) Add PS microspheres to ethanol, sonicate for 30-50 min, then add ethyl orthosilicate, heat to 50-70°C, react for 18-24 h, cool to room temperature, filter, wash, and dry to obtain a mixture A; (3) Add the mixture A and block copolymer P123 obtained in (2) to ethanol, ultrasonicate for 20-40 minutes, then add tetraethyl orthosilicate, heat to 40-50°C, react for 8-12 hours, filter, wash, heat to 500-600°C in a muffle furnace at a heating rate of 1-5°C, keep warm for 3-5 hours, and cool to room temperature to obtain silicon dioxide with high porosity; (4) adding the high-porosity silica obtained in (3) to ethanol, ultrasonicating for 20-40 min, adding the copper / cobalt bimetallic MOFs and light stabilizer obtained in (1), heating to 25-35° C., reacting for 6-8 h, filtering, washing, and drying to obtain a mixture B; (5) Under nitrogen protection, add perfluoro-n-propyl vinyl ether, trifluorochloroethylene, 3-methylacrylamidophenylboronic acid, cystine dimethyl ester and sodium dodecyl sulfate into deionized water, stir for 20-40 min, then add 2-cyanopropyl-2-benzodisulfide and potassium persulfate, heat to 60-80°C, react for 8-12 h, cool to room temperature, add hydroquinone, stir for 30-40 min, centrifuge, wash and dry to obtain a fluorine-containing polymer containing disulfide bonds and borate ester bonds; (6) Mix the mixture B obtained in (4), the fluorinated polymer containing disulfide bonds and borate bonds obtained in (5), and N,N-dimethylformamide, heat to 80-100° C., react for 8-12 hours, cool to room temperature, centrifuge, wash, dry, and pass through a 300-400 mesh sieve to obtain modified silica powder.

2. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The dispersant refers to DX-915 or DX-407 produced by Metachemie; the curing agent refers to toluene diisocyanate or isophorone diisocyanate; the defoamer refers to BYK-052 or BYK-053 produced by BYK; and the leveling agent refers to EFKA-3777 produced by Efka or BYK-333 produced by BYK.

3. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The weight ratio of copper chloride, cobalt acetate, terephthalic acid, ethylene glycol and N,N-dimethylformamide in (1) is 3-6:1-2:0.6-1:3-5:15-25.

4. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: In the (2), the weight ratio of PS microspheres, tetraethyl orthosilicate and ethanol is 0.8-1:0.9-1.5:10-14, and the particle size of the PS microspheres is 50-100 nm.

5. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The weight ratio of the mixture A, block copolymer P123, tetraethyl orthosilicate and ethanol in (3) is 1:0.1-0.2:1-1.2:10-14.

6. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The weight ratio of silica with high porosity, copper / cobalt bimetallic MOFs, light stabilizer and ethanol in (4) is 1:0.2-0.4:0.3-0.5:10-14.

7. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The light stabilizer in (4) is prepared by mixing nano zinc oxide and nano cerium oxide in a weight ratio of 2:

1.

8. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The weight ratio of perfluoro-n-propyl vinyl ether, trifluorochloroethylene, 3-methylacrylamidophenylboric acid, dimethyl cysteine, sodium dodecyl sulfate, 2-cyanopropyl-2-ylbenzodisulfide, potassium persulfate, hydroquinone and deionized water in (5) is 1:0.5-1:0.2-0.5:0.2-0.5:0.01-0.05:0.005-0.015:0.002-0.01:0.01-0.03:15-25.

9. The weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to claim 1, characterized in that: The weight ratio of the mixture B, the fluorine-containing polymer containing disulfide bonds and borate bonds and N,N-dimethylformamide in (6) is 1:0.2-0.4:10-14.

10. The method for preparing the weather-resistant decorative waterborne polyurethane mortar colored sand self-leveling floor material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding a dispersant to a water-based polyurethane emulsion, stirring for 10-20 minutes, adding modified silicon dioxide powder, stirring for 20-30 minutes, and then adding a curing agent, silicate cement, lightweight resin colored sand, a defoaming agent and a leveling agent. After mixing and stirring for 1-3 hours, the mixture is applied to the coated surface with a serrated scraper, and after curing, a weather-resistant decorative water-based polyurethane mortar colored sand self-leveling floor material is obtained.

Citation Information

Patent Citations

  • Polyurea self-repairing thermoplastic elastomer and preparation method thereof

    CN108659188A

  • Double-metal MOF (Metal-Organic Framework) catalyst as well as preparation method and application thereof

    CN108772103A

  • Anti-aging high-transparency high-strength polypropylene plastic barrel and preparation method thereof

    CN109705473A

  • Self-repairing acrylate material and preparation method thereof

    CN114149543A

  • Waterborne polyurethane floating color sand self-leveling mortar and preparation process thereof

    CN115010403A